What role can Prezi play in students’ learning process? - Prowse, Martin (Improving University Science Teaching and Learning, 2023)
This project offers an initial evaluation of using the online learning platform Prezi as a tool for increasing student learning within a MA unit in human geography. It does this by comparing the use of Prezi to four other learning activities conducted during the course. The aim of the project is to see whether the use of this technology became an end in itself, thereby distracting students and detracted from their learning, or whether it added some value to the course. Data comes mainly from five semi-structured interviews with participants. The qualitative data suggests that students appreciated Prezi because it allowed them to be more creative, to select and condense knowledge and to offer a new dimension to presenting knowledge. But, overall, lectures, discussion and group presentations were more important than Prezi in terms of their learning process. The only activity which was less important than Prezi was the other addition to the course: formal debates. Prezi appears to be able to complement students’ learning when they have been able to acquire knowledge through other teaching activities. In essence, it can enhance learning based on more traditional, tried and tested teaching techniques.